Efectuati 9*6*[9-6:(9-6)]:(9-6)
Răspunsuri la întrebare
Răspuns de
0
9*6*[9-6:(9-6)]:(9-6)=
9*6*(9-6:3):3=
9*6*(9-3):3=
9*6*6:3=
45*3=
=135
9*6*(9-6:3):3=
9*6*(9-3):3=
9*6*6:3=
45*3=
=135
Răspuns de
4
9×6×(9-6÷3)÷3=
9×6×(9-2)÷3=
9×6×7÷3=
54·7÷3=
162÷3=
54 .....Sper ca te-am ajutat...
9×6×(9-2)÷3=
9×6×7÷3=
54·7÷3=
162÷3=
54 .....Sper ca te-am ajutat...
vioaraviorica2:
coroana?
Alte întrebări interesante
Biologie,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Fizică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă